AGTRAP Is a Prognostic Biomarker Correlated With Immune Infiltration in Hepatocellular Carcinoma - Liu, Shanshan; Zhao, Wei; Li, Xuemei; Zhang, La; Gao, Yu; Peng, Qiling; Du, Chengyou; Jiang, Ning (Frontiers in Oncology, 2021)
Background Recently, it has been reported that angiotensin II receptor-associated protein (AGTRAP) plays a substantial role in tumor progression. Nevertheless, the possible role of AGTRAP in hepatocellular carcinoma (HCC) remains unrecognized. Methods The metabolic gene rapid visualizer, Cancer Cell Line Encyclopedia, Human Protein Atlas, and Hepatocellular Carcinoma Database were used to analyze the expression of AGTRAP in HCC tissues and normal liver tissues or adjacent tissues. Kaplan-Meier plotter and UALCAN analysis were used to assess the prognostic and diagnostic value of AGTRAP. LinkedOmics and cBioPortal were used to explore the genes co-expressed with AGTRAP in HCC. To further understand the potential mechanism of AGTRAP in HCC, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment pathway analyses were performed using R software, the protein-protein interaction (PPI) network was established using the STRING database, and the immune infiltration and T-cell exhaustion related to AGTRAP were explored via Timer and GEPIA. In addition, immunohistochemistry was used to detect the expression of AGTRAP protein in HCC tissues and paired adjacent tissues from clinical specimens. Results This study found that the mRNA and protein levels of AGTRAP in HCC tissues were higher than those in normal liver tissues and adjacent tissues, and higher mRNA levels of AGTRAP were associated with higher histological grade and a poor overall survival in HCC patients. The area under the receiver operating characteristic curve (AUC) of AGTRAP was 0.856, suggesting that it could be a diagnostic marker for HCC. Moreover, the alteration rate of AGTRAP in HCC was 8%, and AGTRAP was involved in HCC probably through the NF-κB and MAPK signaling pathways. Furthermore, AGTRAP was positively correlated with the infiltration of CD8+ T cells, CD4+ T cells, B cells, macrophages, dendritic cells, and neutrophils, and the levels of AGTRAP were significantly correlated with T-cell exhaustion biomarkers. The immunohistochemistry results confirmed that the protein levels of AGTRAP were consistently higher in HCC tissues than in paired adjacent tissues. Conclusion The clinical value of AGTRAP and its correlation with immune infiltration in HCC was effectively identified in clinical data from multiple recognized databases. These findings indicate that AGTRAP could serve as a potential biomarker in the treatment of HCC, thereby informing its prognosis, diagnosis, and even immunotherapy.